NUP98 Rearrangements in AML: Molecular Mechanisms and Clinical Implications - Sagarajit Mohanty (Onco, 2023)
NUP98 fusions constitute a small subgroup of AML patients and remain a high-risk AML subtype. There are approximately 30 types of NUP98 fusions identified in AML patients. These patients show resistance to currently available therapies and poor clinical outcomes. NUP98 fusions with different fusion partners have oncogenic transformation potential. This review describes how the NUP98 gene acquires oncogenic properties after rearrangement with multiple partners. In the mechanistic part, the formation of nuclear bodies and dysregulation of the HoxA/Meis1 pathway are highlighted. This review also discusses mutational signatures among NUP98 fusions and their significance in leukemogenesis. It also discusses the clinical implications of NUP98 fusions and their associated mutations in AML patients. Furthermore, it highlights therapeutic vulnerabilities in these leukemias that can be exploited as therapeutic strategies. Lastly, this review discusses the gaps in our knowledge regarding NUP98 fusions in AML, as well as future research opportunities.